2008
DOI: 10.1002/aqc.1001
|View full text |Cite
|
Sign up to set email alerts
|

Relative impacts of native and non‐native crayfish on shelter use by an indigenous benthic fish

Abstract: ABSTRACT1. The North American signal crayfish Pacifastacus leniusculus has been widely introduced throughout Europe where it is expanding its range and in many areas replacing the native white-clawed crayfish Austropotamobius pallipes. There is concern with regards to the impact of this species replacement on benthic fish. Interspecific behavioural interactions and competition for shelter between the benthic fish, bullhead Cottus gobio and A. pallipes and P. leniusculus were measured to assess the comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 28 publications
2
41
0
1
Order By: Relevance
“…These results show that introduced across Europe, where impacts upon aquatic flora and fauna have been extensively documented (e.g. Unestam and Weiss 1970;Nyström et al 2001;Stenroth and Nyström 2003;Bubb et al 2006;Olden et al 2006;Bubb et al 2009;Axelsson et al 1997).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…These results show that introduced across Europe, where impacts upon aquatic flora and fauna have been extensively documented (e.g. Unestam and Weiss 1970;Nyström et al 2001;Stenroth and Nyström 2003;Bubb et al 2006;Olden et al 2006;Bubb et al 2009;Axelsson et al 1997).…”
Section: Introductionsupporting
confidence: 53%
“…Charlebois and Lamberti 1996;Axelsson et al 1997;Parkyn et al 1997;Nyström et al 2001;Dorn and Mittelbach 2004;Usio and Townsend 2004;McCarthy et al 2006;Jackson et al 2014;Moorhouse et al 2014), demonstrated by their consistently strong negative effects on plant biomass, other macroinvertebrates, fish and amphibian eggs and larvae. Additionally, crayfish are likely to directly compete with other organisms for resources (Bubb et al 2009). Indeed the current study provides some evidence of resource competition in finding that the refuge use of fish was significantly lower in the presence of invasive, but not native, crayfish.…”
Section: Discussionmentioning
confidence: 99%
“…Further, since signals chiefly hide under stones, they displace not only native crayfish but small fish sharing this habitat, such as salmon parr Salmo salar, bullhead Cottus gobio and stone loach Barbatula barbatula. By depriving the displaced fish of shelter they increase their susceptibility to predation, with potentially deleterious effects (Rahel and Stein, 1988;Guan and Wiles, 1997;Griffiths et al, 2004;Bubb et al, 2009). Competition for winter shelter has been experimentally demonstrated among exotic signal crayfish and native juvenile Atlantic salmon (Griffiths et al, 2004).…”
Section: > Signal Crayfish Pacifastacus Leniusculusmentioning
confidence: 99%
“…Where more than one fish species is present the interactions may vary, for example, small fish species can be displaced from shelter by crayfish, increasing their vulnerability to predation by piscivorous species (Rahel and Stein, 1988;Light, 2005); or the fish may show reduced growth in the presence of crayfish (Carpenter, 2005). Benthic fish appear to be particularly vulnerable to the effects of predation or competition by crayfish, with reductions in sculpin species in the USA (Light, 2005), and in bullhead Cottus gobio in England Wiles, 1997, 1998;Bubb et al, 2009). Whilst Bubb et al (2009) found some disturbance of bullhead by the indigenous white-clawed crayfish Austropotamobius pallipes, non-indigenous signal crayfish were much more aggressive towards the fish in laboratory trials, causing damage to fins and in some cases, mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Benthic fish appear to be particularly vulnerable to the effects of predation or competition by crayfish, with reductions in sculpin species in the USA (Light, 2005), and in bullhead Cottus gobio in England Wiles, 1997, 1998;Bubb et al, 2009). Whilst Bubb et al (2009) found some disturbance of bullhead by the indigenous white-clawed crayfish Austropotamobius pallipes, non-indigenous signal crayfish were much more aggressive towards the fish in laboratory trials, causing damage to fins and in some cases, mortality. The same authors found reductions in abundance of bullhead in rivers too when signal crayfish were present.…”
Section: Introductionmentioning
confidence: 99%